2020
DOI: 10.7554/elife.58041
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fatty acid synthesis coordinates oxidative metabolism in mammalian mitochondria

Abstract: Cells harbor two systems for fatty acid synthesis, one in the cytoplasm (catalyzed by fatty acid synthase, FASN) and one in the mitochondria (mtFAS). In contrast to FASN, mtFAS is poorly characterized, especially in higher eukaryotes, with the major product(s), metabolic roles, and cellular function(s) being essentially unknown. Here we show that hypomorphic mtFAS mutant mouse skeletal myoblast cell lines display a severe loss of electron transport chain (ETC) complexes and exhibit compensatory metabolic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 93 publications
4
59
0
1
Order By: Relevance
“…The synthesis of new long-chain fatty acids from non-lipid substrates is another input to the intracellular free fatty acid pool. We will focus on the cytosolic pathway but acknowledge that mitochondria are capable of synthesizing predominantly short- and medium-chain fatty acids that can act as precursors for lipoic acid synthesis and protein lipoylation [ 72 , 73 ]. The cytosolic synthesis of fatty acids starts with the export of mitochondrial citrate into the cytosol via the mitochondrial tricarboxylate transporter (encoded by SLC25A1) where it is converted into acetyl-CoA by ATP-citrate lyase (encoded by ACLY; Fig.…”
Section: Tumor Fatty Acid Metabolism Pathways and Their Role In Cancementioning
confidence: 99%
“…The synthesis of new long-chain fatty acids from non-lipid substrates is another input to the intracellular free fatty acid pool. We will focus on the cytosolic pathway but acknowledge that mitochondria are capable of synthesizing predominantly short- and medium-chain fatty acids that can act as precursors for lipoic acid synthesis and protein lipoylation [ 72 , 73 ]. The cytosolic synthesis of fatty acids starts with the export of mitochondrial citrate into the cytosol via the mitochondrial tricarboxylate transporter (encoded by SLC25A1) where it is converted into acetyl-CoA by ATP-citrate lyase (encoded by ACLY; Fig.…”
Section: Tumor Fatty Acid Metabolism Pathways and Their Role In Cancementioning
confidence: 99%
“…We became interested to unravel what this essential function might be. Recent studies in yeast and human cells have identified an expanding network of mitochondrial ACP interactions beyond FASII that includes roles in respiratory chain assembly, Fe-S cluster biogenesis, and mitochondrial ribosomal translation (19)(20)(21)(22)(23). However, in all cases these critical interactions in yeast and/or humans are linked to mitochondrial FASII function and the Ppant group of ACP (22,(24)(25)(26).…”
Section: Significance Statementmentioning
confidence: 99%
“…Lipoic acid is found in all kingdoms of life and is an essential cofactor for several cellular redox reactions [ 49 ]. Several inborn errors of metabolism also characterized by defective lipoylation have been described [ 49 ], such as lipoic acid synthetase (LIAS) [ 93 , 94 ] and lipoyltransferase 1 (LIPT1) deficiencies [ 95 ]. As in most of the identified patients the onset of clinical manifestations appeared later in life [ 50 ], and pre-symptomatic patient management may have contributed to reduce the initial risk of symptoms development [ 52 ], we hypothesize that compensatory mechanisms in mitochondrial energetics may specifically address the required energy need.…”
Section: Mitochondrial Metabolism Of Fatty Acidsmentioning
confidence: 99%